Perceptions of educators regarding the implementation of the health promotion programme manuals for children in schools in Makapanstad, South Africa - Doriccah Peu; Sanah Mataboge; Rendani Ladzani; Lene Wessels; Karien Mostert-Wentzel; Neo Seane (AOSIS, 2015)
Background: Health promoting schools focus on, amongst other things, preventing leading causes of death such as Sexually Transmitted Infections (STI's), Human Immune Deficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS), a sedentary lifestyle and creating conditions that are conducive to health through health education. Aim: This study explored the perceptions of educators regarding implementation of the health promotion programme manuals in selected schools of the Makapanstad community. Method: A qualitative, exploratory, descriptive and contextual design was utilised in this study. Four schools were selected to participate in the study. Purposive sampling was used to select educators from these schools who were actively involved in the health promotion programme. Data collection was taken through focus group interviews. One focus group comprised of eight participants who were interviewed three times. The focus group interviews were conducted until data were saturated. Data were analysed using an adaptation of Tesch's method. The eight steps of Tesch's method enabled researchers to systematically analyse and organise data using colour coding to develop data into categories, sub-categories and themes. Results and conclusion: The themes that emerged during data analysis were: the perceptions of educators regarding health promotion programme manuals before implementation of manuals, and the perceptions of educators regarding health promotion programme manuals after the implementation of manuals. Introducing health promotion materials to the schools served as a point of departure for developing personal skills and creating a supportive environment for health in schools. The health promotion manual assisted the educators to attain appropriate health promotion information.